Correlation between sleep and quality of life in cerebral palsy - Zuculo, Gabriela Melloni [UNESP]; Knap, Cintia Cristina Fadini [UNESP]; Pinato, Luciana [UNESP] (Sociedade Brasileira de Fonoaudiologia, 2014)
PURPOSE: To investigate and correlate the sleep pattern and quality of life in individuals with cerebral palsy (CP) compared to healthy controls. METHODS: Seventy-eight subjects (aged 4-18 years, both genders) comprised two groups: CP, composed of 43 individuals with CP, and control, composed of 35 individuals without neurodevelopmental disorders. General Sleep Habits Questionnaire, Sleep Disturbance Scale for Children, sleep diary, Child Health Questionnaire, and Children's Quality of Life Scale were used. RESULTS: This study identified that 60.5% individuals with CP had sleep disorders. The respiratory disorders (25.6%) and the sleep hyperhidrosis (34.9%) were the most common disturbances in the group with CP. Moreover, 23.2% individuals of the group with CP reported awaking in the middle of the night and 37.2% of them snore, both percentages were higher than those in the control group. The sleep diary showed that individuals in the group with CP spend more time to initiate sleep (around 21 minutes). The group with CP also showed deficits in all parameters analyzed by the Child Health Questionnaire, except in family activity and the sleep-wake pattern, and quality of life showed negative correlation in several respects. CONCLUSION: The altered pattern of sleep in individuals with CP directly affects their physical and emotional well-being.

OBJETIVO: Investigar e correlacionar o padrão sono-vigília e a qualidade de vida na paralisia cerebral (PC). MÉTODOS: Setenta e oito indivíduos, de 4 a 18 anos de idade, de ambos os gêneros, compuseram dois grupos: PC, composto por 43 indivíduos com PC; e controle, com 35 indivíduos sem distúrbios no neurodesenvolvimento. Os procedimentos utilizados foram: Questionário de Hábitos de Sono, Escala de Distúrbios do Sono em Crianças, Diário de sono, Questionário de Saúde da Criança e Escala de Qualidade de Vida da Criança. RESULTADOS: Identificou-se que 60,5% dos indivíduos com PC apresentaram distúrbios do sono, sendo os mais comuns, os respiratórios e a hiperhidrose do sono, com 25,6 e 34,9%, respectivamente. Além disso, 23,2% dos indivíduos do grupo PC acordam no meio da noite e 37,2% deles roncam, percentuais estes maiores do que os do grupo controle. O Diário de sono mostrou que os indivíduos do grupo PC demoraram mais para iniciar o sono (em média 21 minutos) do que o grupo controle. Quanto à qualidade de vida, o grupo PC apresentou déficit em todos os parâmetros analisados, exceto em atividade familiar e os distúrbios de sono encontrados e a qualidade de vida indicaram correlação negativa na maioria dos parâmetros. CONCLUSÕES: O padrão de sono alterado nos PCs afeta diretamente aspectos do seu bem-estar físico e emocional.
Correlação entre sono e qualidade de vida na paralisia cerebral